The Macroeconomics of Model T - Reto Föllmi; Tobias Wuergler; Josef Zweimüller (Verein für Socialpolitik, 2010)
We study a model of endogenous growth where firms invest both in product and process innovations. Product innovations (that open up completely new product lines) satisfy the advanced wants of the rich. Subsequent process innovations (that decrease costs per unit of quality) transform the luxurious products of the rich into conveniences of the poor. A prototypical example for such a product cycle is the automobile. Initially an exclusive product for the very rich, the automobile became affordable to the middle class after the introduction of Ford's Model T, the car that put America on wheels. We show that an egalitarian society creates strong incentives for process innovations (such as the Model T) whereas an unequal society creates strong incentives for product innovations (new luxuries). We show that the inequality-growth relationship depends on which type of innovative activity drives technical progress, analyzing both the characteristics of and the transition to the balanced growth path.
Keywords: O30; O15; D30; 330; inequality; technical change; growth; mass production; product innovations; process innovations